FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP KEBERLANJUTAN KAWASAN PERMUKIMAN DI DAERAH ALIRAN SUNGAI (DAS) CILIWUNG HULU KABUPATEN BOGOR - Dewi, Indarti Komala (-)
The upper stream of Ciliwung watershed lies in Bogor District, has an important function for the surrounding areas, which regulated or managed water supply, whether floods or drought in the middle and the down stream.  Growing of settlement areas was changed landscape and degraded environment, and then this is threated sustainability of setlement areas. Sustainability of Settlement areas in Upper stream of Ciliwung Watershed are impacted  by  internal and external factors. The objective of this research the first is to analyse sustainability of settlement areas in upper stream of Ciliwung Watershed. and the second is to analyse  factors that impacting sustainability of  settlement areas in the upperstream of Ciliwung watershed, The research method used Multi Dimentional Scaling (MDS) technique with Rapfish software. The research result showed that settlement areas in Upper stream of Ciliwung watershed are less sustainable, with 16 factors that impacting this sustainability. Keyword :  Ciliwung watershed, sustainability of settlement areas.